2016
DOI: 10.5125/jkaoms.2016.42.3.144
|View full text |Cite
|
Sign up to set email alerts
|

Transbuccal versus transoral approach for management of mandibular angle fractures: a prospective, clinical and radiographic study

Abstract: ObjectivesWe compared the transbuccal and transoral approaches in the management of mandibular angle fractures.Materials and MethodsSixty patients with mandibular angle fractures were randomly divided into two equal groups (A, transoral approach; group B, transbuccal approach) who received fracture reduction using a single 2.5 mm 4 holed miniplate with a bar using either of the two approaches. Intraoperatively, the surgical time and the ease of surgical assess for fixation were noted. Patients were followed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…In our study of 30 cases with mandibular angle fracture mean age was 25.07 years (range, 7-56 years), with male predominance (90%) and road traffic accidents as a most common e ology 18 (60%) and right side predominance 18(60%). The finding of this study is comparable to that by 3 13…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In our study of 30 cases with mandibular angle fracture mean age was 25.07 years (range, 7-56 years), with male predominance (90%) and road traffic accidents as a most common e ology 18 (60%) and right side predominance 18(60%). The finding of this study is comparable to that by 3 13…”
Section: Resultssupporting
confidence: 91%
“…The mean opera ve dura on was lesser in transbuccal approach (111.25 minutes) compared to transbuccal (lower border) approach (120 minutes) and intraoral (122.5 minutes) in case of isolated angle fracture. The mean opera ve me is greater in our study because we took total anesthe c dura on ( me from intuba on to me of 3,8,12,13 extuba on) where as other studies took me from incision to closure. Our study showed greater me for transbuccal (lower border) approach because two miniplates were used for fixa on.…”
mentioning
confidence: 96%
“…Owing to the characteristics of the extraoral approach, scarring may occur in the facial area, and the intraoral approach tends to be used as much as possible, but scarring can be reduced sufficiently through accurate incision and suture. Many papers have reported that access to the surgical site is easier, and the reduction of the fracture fragment is more accurate when operating with the extraoral approach [ 7 ].…”
Section: Main Textmentioning
confidence: 99%
“…Other modalities like transbuccal trochar system is again an indispensable tool, but greatly challenged by the fact that it severely limits the visualization of the fracture site [ 8 ]. It makes the manipulation of bony fragments difficult and fixation screws and plates are highly difficult to place in the area of interest.…”
Section: Discussionmentioning
confidence: 99%